Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s12552-016-9162-0
|View full text |Cite
|
Sign up to set email alerts
|

Young, Black, and (Still) in the Red: Parental Wealth, Race, and Student Loan Debt

Abstract: Taking out student loans to assist with the costs of postsecondary schooling in the US has become the norm in recent decades. The debt burden young adults acquire during the higher education process, however, is increasingly stratified with black young adults holding greater debt burden than whites. Using data from the NLSY 1997 cohort, we examine racial differences in student loan debt acquisition and parental net wealth as a predictor contributing to this growing divide. We have four main results. First, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(156 citation statements)
references
References 54 publications
(57 reference statements)
4
149
2
1
Order By: Relevance
“…Given that blacks experience lower labor market returns to college than whites (Gaddis 2015), while also facing higher debt burdens and dropout risk, black young adults take a great deal more risk in enrolling in college, and reap fewer rewards to that risk. This growing body of evidence suggests that rising debt may contribute to growing racial differences in the transition to adulthood (Furstenberg et al 2004), and may contribute to the fragility of the next generation of the black middle class (Addo, Houle and Simon 2016). To the extent that student debt may reinforce and reproduce racial inequalities within and across generations, future research should continue to interrogate the causes and consequences of racial disparities in debt, and heterogeneity in the consequences of debt by race.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that blacks experience lower labor market returns to college than whites (Gaddis 2015), while also facing higher debt burdens and dropout risk, black young adults take a great deal more risk in enrolling in college, and reap fewer rewards to that risk. This growing body of evidence suggests that rising debt may contribute to growing racial differences in the transition to adulthood (Furstenberg et al 2004), and may contribute to the fragility of the next generation of the black middle class (Addo, Houle and Simon 2016). To the extent that student debt may reinforce and reproduce racial inequalities within and across generations, future research should continue to interrogate the causes and consequences of racial disparities in debt, and heterogeneity in the consequences of debt by race.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 69% of blacks who dropout cite student debt as a primary reason for not completing their degree, compared to 43% of white students (Johnson, Van Ostern and White 2012). After leaving college, blacks also report being significantly more concerned about being able to afford student loan payments than whites (Ratcliffe and McKernan 2013), and have more difficulty paying off equivalent amounts of debt than white young adults (Addo, Houle and Simon 2016), which may be a result of high interest rates, and because of lower labor market returns to a college degree. That is, black young adults not only face higher debt burdens than their white counterparts, and thus are exposed to greater risks in their college experience, but they are also experience fewer rewards to a college degree (Addo, Houle and Simon 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students of different race/ethnicity backgrounds tend to differ in borrowing behaviors. On the undergraduate level, research findings show general aversion of borrowing for Asian students and the opposite as well as higher risk of default and difficulty in repaying student debt for Black students (Addo, Houle, & Simon, 2016;Baum & Steele, 2010;Huelsman, 2015;Jackson & Reynolds, 2013;Malcom & Dowd, 2012;Price, 2004). Hispanic students are more likely to have excessive student debt a few years after graduation than White students (Price, 2004), suggesting difficulty in repaying student debt.…”
Section: Racial Disparities In Student Borrowingmentioning
confidence: 98%
“…Over the past 30 years, college enrollment rates for Black and White students have converged (65 percent vs. 70 percent in 2013; Casselman, 2014); however, six-year completion rates have not (40 percent vs. 62 percent), leaving many young Blacks with student debt but no degree. In part because of this, wealth disparities begin to appear early in adulthood: In a recent analysis of young people with some post-secondary education, Whites report $17,000 more in net wealth at age 25 than Blacks the same age (Addo, Houle, and Simon, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, a recent study found that White students report an average of $12,000 in financial assistance from parents, while Black students report an average of only $4,000 (Addo et al, 2016), likely a result of differences in available resources. However, another recent study (Nam et al, 2015, p. 10) notes that "Black parents who help finance their children's education do so with far lower levels of income and wealth than White parents who choose not to do so," indicating a strong commitment to education among Black families.…”
Section: Literature Reviewmentioning
confidence: 99%